Examination of Predicting Factors for COVID-19 Vaccination Behaviors of University Students Utilizing the Theory of Planned Behavior - Heo, Yeon Jeong; Hyun, Hye-Jin (Journal of Korean Academy of Nursing, 2024)
This study aimed to examine the predictive factors of COVID-19 vaccination behavior by evaluating the moderating effect of perceived behavioral control on the theory of planned behavior. Data were collected from August 6 to August 31, 2022 from 235 college students (aged 20~29 years) across 12 universities using a structured web-based survey. Statistical analyses were conducted using the SPSS and AMOS software. Attitudes toward COVID-19 vaccination, subjective norms, and intention to be vaccinated significantly influenced COVID-19 vaccination behavior. Attitudes and subjective norms indirectly affected COVID-19 vaccination behavior through intention to vaccinate, whereas intention to vaccinate had a direct effect. The moderating effect of perceived behavioral control on the relationship between subjective norms and intention to vaccinate was significant. Interventions that foster a positive attitude toward COVID-19 vaccination and bolster subjective norms and perceived behavioral control can boost the intention to be vaccinated and facilitate the uptake of COVID-19 vaccination.